RURAL WOMEN’S CYCLE OF BITTERNESS ON SHORT-VIDEO PLATFORMS IN CHINA - Huang, Bingxi (AoIR Selected Papers of Internet Research, 2026)
“Bitterness [苦]” is a prominent affect in Chinese culture, rooted in sensory and emotional experiences and extending to an existential awareness of life’s uncertainty. Since time immemorial, bitterness has been linked to the hardships of agricultural labour and patriarchal exploitation. During the Maoist era, bitterness, particularly embodied by rural women, was reframed as a feudal remnant to be eliminated through rituals like "spitting out bitterness" for a socialist future. Meanwhile, rural women were expected to “eat more bitterness”, forming a cycle of bitterness. This cycle now recurs on short-video platforms. Through textual analysis, interviews, and observations of ten rural female content creators in China, this paper explores their self-representation of suffering. Building on critiques of self-branding in digital cultures (Banet-Weiser, 2013), I argue that Chinese rural women repackage bitterness as a commodity within platforms’ attention economy. The bitterness they "spit out" through short video essentialises rural identities as inferior and backward for urban audiences, who see these qualities as virtues rather than stemming from structural inequalities. Fundamental aspects of rural bitterness, such as the urban-rural division, remain intact. Rural women must continue to "eat" bitterness, now even more tied to their rural subjectivities. During this process, inspired by Butler’s theory of “grievability” (2010), bitterness is seen as affective governance tied to social conditioning, intersecting with personal feelings. Paradoxically, it also lets these women monetise the very affects associated with their hardships and marginalised status through the attention economy.